(untitled) (Palimpsesto, 2023)
Studies in Chile indicate the transversal effects in the educational system of the Educational Environment. The Educational Environment in higher education is based on inhabiting the autonomy of the student body and the perception that the educational space generates in the Student Experience. Its dimensions are infrastructure, material resources, social relations and actors in the educational environment. The bibliography of the repository of Chilean scientific journals was reviewed using PRISMA procedures. The results indicate how the Educational Environment affects the educational processes, the importance of individuality, in its strengths and weaknesses, for inhabiting educational spaces and, the design of the differences in cognitive, affective and motivational skills, being a lever of the learnings.